HAMBATAN KOMUNIKASI ANTARBUDAYA DI KALANGAN MAHASISWA - Moulita Moulita (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
ABSTRACTEducational opportunities the wide open for college students also opened a high for it is he Cross-cultural communication both in the campus where they learn as well as society environment tempatan. In fact, many obstacles Cross-cultural communication experienced by the students were in the process educated .Various research studies show some problems that frequently encountered in between that is language, stereotypes and prejudice, the interpretation nonverba , a tendency to judge, and anxiety high. Needs to develop attitudes and ability as openness mind, tolerance, and empathy to overcome the Cross-cultural communication that might be occurred in interaction the students were Keyword: Cross-cultural communication, obstacles, students